Antibacterial effect of an experimental endodontic cement with the incorporation of natural compounds (mint, muña, propolis tincture, and Jalk propolis): an in vitro experimental study - Pickling Gonzales-Posada, Erwin Duilio (2025)
Objective: To determine in vitro the antibacterial effect of an experimental endodontic cement based on different natural compounds (mint, muña, propolis tincture, and Jalk propolis): against Enterococcus faecalis. Materials and methods: The antibacterial effect was determined against the E. faecalis strain (ATCC 2982), using the disk diffusion method. In Petri dishes with brain heart agar (BHA), the strain was disseminated, and the four natural compounds were placed on Whatman paper disks to incubate for 24 hours under anaerobic conditions. The diameters of the inhibition halos were measured with a digital vernier caliper. The data obtained were statistically examined using analysis of variance (ANOVA) and Tukey's post-hoc test. Results: The muña compound showed the greatest inhibition halo (5.975 ± 0.050 mm), followed by mint, Jalk propolis, and propolis tincture, in that order. The control endodontic cement showed the greatest inhibition halo (18.050 ± 0.451 mm), followed by the mint-containing cement (16.498 ± 0.460 mm). Conclusions: The muña compound presented the highest antibacterial activity against E. faecalis, while propolis tincture had the lowest antibacterial activity. On the other hand, experimental endodontic cement with natural compounds decreased the antibacterial activity concerning pure cement.